(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2019)
The paper explores the relationship between land rights campaigns and self-determination for Indigenous Australians, and argues that Native Title has effectively complicated and undermined the land recovery process that Indigenous Australians achieved under various State land rights acts. Keywords Land rights, Native Title, self determination